Integrating AI-Based Pronunciation App ELSA Speak in English Lessons: A Case Study at SMP Negeri 4 Batanghari Nuban - Erry Raihan; Mai Zuniati; Umar Al Faruq Al Hasyim; Suhono Suhono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
The development of digital technology has significantly influenced the way English is taught and learned, particularly in pronunciation practice. One of the applications that can assist students in improving their pronunciation is ELSA Speak, which provides automatic feedback on spoken English. This study aimed to examine the implementation of ELSA Speak in English pronunciation learning and to explore students’ responses to its use in the classroom. This study used a qualitative case study design conducted at SMP Negeri 4 Batanghari Nuban. The participants consisted of one English teacher and 31 eighth-grade students, with five students selected for in-depth interviews. The data were obtained through interviews and analyzed using descriptive qualitative analysis. The results showed that the application supported students in practicing pronunciation more regularly and helped them recognize and correct their pronunciation errors through instant feedback. In addition, students responded positively because the application made the learning process more interactive and engaging. However, several obstacles were also identified, such as unstable internet connections and students’ difficulties in pronouncing certain English sounds. The findings also indicate that the teacher plays an important role in guiding students in using the application effectively during the learning process. The teacher’s guidance helps students understand how to use the feedback provided by the application to improve their pronunciation. Therefore, the integration of technology-based applications such as ELSA Speak can be considered as an alternative tool to support pronunciation learning in English classrooms. This study also suggests that the use of digital pronunciation applications can enhance students’ engagement and provide additional opportunities for independent pronunciation practice.